Evaluative Practices in the Systems Engineering Major of the National University of Engineering of Nicaragua (2012-2017) - Gómez Jaime, Dora Isabel (2023)
This investigation sought to understand the consistency of the discourses and evaluative practices of the university authorities and teaching staff of the Systems Engineering major at the National University of Engineering (UNI) during the period of 2012-2017. The researchers developed this study under a qualitative paradigm and a point of view of Symbolic Interactionism; furthermore, they applied a methodological approach to the intrinsic case study. Interviews and content analysis were the methods used and, correspondingly, individual semi-structured interviews and documentary analysis were chosen as techniques. Eighteen key informants were selected, including teachers and authorities who met the defined common criteria and the non-common criteria as the case may be. Based on the theories of learning evaluation, the authors studied the institutional and oral discourses of the informants. As a main result, the researchers confirm that performance techniques prevail in the Systems Engineering degree, highlighting the use of objective exams or tests, course projects, and course tasks as evaluative instruments. Moreover, a correspondence between the institutional written discourse from the Academic Regime Regulations (RRA) of the university and the evaluation practices of the teaching staff is evident. As well, there is a coherence between the oral and written discourse on the evaluation of learning in the major under study, which leans towards a behavioral evaluative perspective. The evaluation of learning in the degree and therefore in the university is applied by the behavioral model, through techniques and instruments that allow the verification of the knowledge acquired by the students. The main contribution is to educational evaluation, to the evaluation of learning, with a Proposal to implement coherence between discourse and evaluation practice at the UNI and in the Systems Engineering career.